Test Results Of Temperature Variation On Hair Dryer Fishing Equipment (Cabinet Type) - Erdi K.L. Tobing; Ainun Rohanah; Saipul Bahri Daulay (Universitas Sumatera Utara, 2016)
Drying is an important activity in pickling food presentation, as well as in agriculture product industry. The easiest and cheapest way to do drying is with sun light or sundrying. To overcome the sunlight limitation, a sunlight fish drying was had to guarantee the fish higenity. This research was aimed to test moisture content of pora-pora fish using fish dryer machine (cabinet type) and calculated the organoleptic value of the result. This research had been conducted at agriculture engineering laboratory, faculty of agriculture USU in December 2014 until March 2015 using pora-pora fish. Parameters observed were moisture content and organoleptic test. The result of this research showed that the best moisture content was 29,17%, the best appearance 7,13 and the smell was 7,0. Keywords: Dryer fish machine (cabinet type), pora-pora fish